PELUANG DAN TANTANGAN PENGEMBANGAN WISATA RELIGI DI TAMAN WISATA IMAN, SITINJO DAIRI - Wiharjokusumo, Padriadi; Saragih, Novita Romauli (Jurnal Ilmiah Akomodasi Agung, 2023)
The Religious Tourism Park (Taman Wisata Iman or TWI) in Sitinjo Dairi is one of the growing religious tourist destinations in North Sumatra. TWI offers various religious and tourist activities that combine the beauty of nature and spiritual values. The purpose of this study is to analyze the opportunities and challenges in the development of religious tourism in TWI. The method used is qualitative research with data collection techniques through interviews, observation, and literature study. The results show that the opportunities for the development of religious tourism in TWI are due to the potential of a beautiful place, a conducive environment, and a spiritual experience that can provide satisfaction for visitors. The challenges of developing religious tourism in TWI include a lack of support from the government, inadequate facilities and infrastructure, and a lack of skilled and experienced human resources in tourism and religion. Therefore, there is a need for government support, better infrastructure development, and human resource development for religious tourism in TWI to develop well. Keywords: Taman Wisata Iman, development, religious tourism, opportunities, challenges.